Emiss\~oes relativas de poluentes do transporte motorizado de passageiros nos grandes centros urbanos brasileiros - Carlos Henrique Ribeiro de Carvalho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– This paper discusses vehicles emissions of pollutants in great urban centers and it makes a brief analysis of adopted public policies in Brazil which have an impact those emissions. Moreover, a methodology to calculate the relative emissions of greenhouse gases is presented on the basis of the unitary average emission of vehicles and the travel modal matrix. We also present the main sources vehicle in the emissions of local pollutants in Brazilian urban centers. We conclude that, beyond traditional policies of control of the unitary emissions, policies of incentive of use of the mass public transport in detriment to the use of the individual transport are basic to reduce the volume of pollutants in the atmosphere of the large cities.
Keywords: R49; 330